2017
DOI: 10.14417/ap.1167
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades psicométricas da versão portuguesa do Obsessive-Compulsive Inventory – Revised

Abstract: Foram examinadas as propriedades psicométricas da versão Portuguesa do Obsessive-Compulsive Inventory -Revised (OCI-R; Foa et al., 2002) em duas amostras não-clínicas (N=509). A estrutura original de seis fatores correlacionados foi confirmada através de uma análise fatorial confirmatória, tendo sido igualmente evidenciada a invariância estrutural segundo o sexo do OCI-R. Os resultados, para a escala total e cada uma das subescalas, revelaram boa consistência interna, validade convergente e divergente e confia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The authors of the original Obsessive–Compulsive Inventory – Revised found an optimal cut-off score of 21 (sensitivity 65.6%; specificity 63.6%). The Portuguese validation presented good psychometric proprieties and confirmed the six related factors structures of the original scale 67 .…”
Section: Methodssupporting
confidence: 54%
“…The authors of the original Obsessive–Compulsive Inventory – Revised found an optimal cut-off score of 21 (sensitivity 65.6%; specificity 63.6%). The Portuguese validation presented good psychometric proprieties and confirmed the six related factors structures of the original scale 67 .…”
Section: Methodssupporting
confidence: 54%
“…The OCI-R showed good psychometric properties in several studies (Abramowitz & Deacon, 2006;Faria & Cardoso, 2017;Fullana et al, 2005;Malpica et al, 2009;Solem et al, 2010). In our study, the Portuguese version of the OCI-R (Faria & Cardoso, 2017) was used, which exhibited good convergent and divergent validity and Cronbach's alpha values ranging from .61 to .90 for the six subscales and .89 for the 18-item scale (Faria & Cardoso, 2017).…”
Section: Participantsmentioning
confidence: 52%
“…Although the vast majority of studies in which the OCI-R was used consider a correlated sixfactor structure (e.g., Abramowitz & Deacon, 2006;Faria & Cardoso, 2017;Olafsson et al, 2013;Solem et al, 2010), the present study examined the bifactor structure of the OCI-R, which was tested against three other models, a single factor model, a correlated six-factor model and a second order model with a general factor loading on the six domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obsessive-compulsive symptoms were measured with the Portuguese version of Obsessive-Compulsive Inventory-Revised (OCI-R; Faria & Cardoso, 2017;Foa et al, 2002), with 18 items that assess the degree of emotional suffering related to these symptoms on a 5-point Likert scale (0 = not at all to 4 = extremely). In addition to the overall score, items are grouped in six factors (3 items each): washing, obsessing, hoarding, ordering, checking and neutralizing.…”
Section: Instrumentsmentioning
confidence: 99%